Temporal regularities allow saving time for maintenance in working memory. Issue 1 (15th March 2018) - Fanuel, Lison; Portrat, Sophie; Tillmann, Barbara; Plancher, Gaën
Abstract: Recent evidence suggests that working memory (WM) performance can be enhanced in the presence of an isochronous rhythm during the retention interval because it improves refreshing. Considering the cognitive load (CL) effect as an indicator of refreshing, the present study investigated whether an isochronous rhythm might benefit memory performance under varying cognitive load. For that goal, the presence of a regular rhythm and the cognitive load of the concurrent task (i.e., reading of digits that were either same or different within a trial) were systematically varied. Recall performance was decreased by high cognitive load compared with low cognitive load but was improved in the regular rhythm condition compared with the silent condition. No interaction between cognitive load and rhythm was observed. The present results suggest that temporal regularities might speed up the reading of the digits rather than improve the efficiency of refreshing, resulting in more time available for refreshing and, consequently, improved memory performance. These findings are interpreted in the framework of the dynamic attending theory and in the scope of recent models of working memory, which are also considering the temporal components of working memory and the importance of the temporal structure of working memory tasks.